2019
DOI: 10.3168/jds.2018-15716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-acetyl-l-methionine supplementation on lactation performance and plasma variables in mid-lactating dairy cows

Abstract: The objective of current study was to investigate the effect of N-acetyl-l-methionine (NALM) supplementation on lactation performance and plasma variables in mid-lactating dairy cows. Forty-eight multiparous cows were blocked into 12 groups based on parity, days in milk, and milk production and were randomly assigned to 1 of the 4 treatments: 0, 15, 30, or 60 g/d of NALM per cow to supplement the basal diet. The experiment was conducted over a 13-wk period, with the first week as adaptation. The yields of milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…N-Acetyl-l-Met supplementation increased milk fat synthesis and feed efficiency in early-lactation (53 ± 10 DIM, SD) dairy cows (Fagundes et al, 2018). Liang et al (2019) observed greater milk yield with NALM supplementation in mid-lactation dairy cows (167 ± 13 DIM); however, no effects were observed on feed efficiency and milk fat synthesis. Although rumen-protected Met (RPM) supplementation in dairy cow diets have been extensively evaluated (Schwab, 1996;Schwab and Broderick, 2017), we are still lacking studies evaluating the long-term efficacy of RPM on production performance of lactating dairy cows.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…N-Acetyl-l-Met supplementation increased milk fat synthesis and feed efficiency in early-lactation (53 ± 10 DIM, SD) dairy cows (Fagundes et al, 2018). Liang et al (2019) observed greater milk yield with NALM supplementation in mid-lactation dairy cows (167 ± 13 DIM); however, no effects were observed on feed efficiency and milk fat synthesis. Although rumen-protected Met (RPM) supplementation in dairy cow diets have been extensively evaluated (Schwab, 1996;Schwab and Broderick, 2017), we are still lacking studies evaluating the long-term efficacy of RPM on production performance of lactating dairy cows.…”
Section: Introductionmentioning
confidence: 78%
“…Despite inconsistent milk yield responses, NALM supplementation increased feed efficiency in previous studies. Liang et al (2019) observed a tendency for greater feed efficiency, expressed as FCM/DMI, for cows supplemented with 30 g of NALM. Similarly, Fa-gundes et al ( 2018) and Osorio et al (2013) reported greater 3.5% FCM/DMI and ECM/DMI for cows supplemented with RPM sources.…”
Section: Production Performancementioning
confidence: 84%
See 2 more Smart Citations
“…Researchers conducting dairy cow experiments can easily and accurately obtain the feed intake data of dairy cows when the cows are fixed in one position [20][21][22]. However, with the modern construction of dairy farms and the emphasis on the animal welfare, almost all commercial dairy farms nowadays are free-stall barn system, in which all cows are fed in a moving and eating freely cowshed [23].…”
Section: Discussionmentioning
confidence: 99%